2009
DOI: 10.1080/07373930902988247
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Neural Network (ANN) and Response Surface Methodology (RSM) in the Prediction of Quality Parameters of Spray-Dried Pomegranate Juice

Abstract: Response surface methodology (RSM) is a frequently used method for empirical modeling and prediction in the processing of biological media. The artificial neural network (ANN) has recently grown to be one of the most efficient methods for empirical modeling and prediction, especially for nonlinear systems. This article presents comparative studies between an ANN and RSM in the modeling and prediction of quality parameters of spray-dried pomegranate juice. In this study, the effects of the carrier type, carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 34 publications
3
69
0
Order By: Relevance
“…Results from this study showed that the estimation capability of ANN for optimum levels of variables for lipase production by recombinant E. coli was more accurate than RSM. Similar observations have also been reported [8,28,29]. Both methods (RSM and ANN) estimated low glucose concentration as optimal levels.…”
Section: Methodssupporting
confidence: 74%
“…Results from this study showed that the estimation capability of ANN for optimum levels of variables for lipase production by recombinant E. coli was more accurate than RSM. Similar observations have also been reported [8,28,29]. Both methods (RSM and ANN) estimated low glucose concentration as optimal levels.…”
Section: Methodssupporting
confidence: 74%
“…Youssefi et al [38] compared ANN and Response Surface Methodology (RSM) in the prediction of quality parameters of spray-dried pomegranate juice. RSM is a frequently used method for empirical modeling and prediction in the processing of biological media.…”
Section: Aa Pomegranatementioning
confidence: 99%
“…Response surface polynomials are local approximations of the real input-and-output relationships and can thus be used as an interesting alternative for conventional models, such as numerical simulations during optimization [14].…”
mentioning
confidence: 99%